RECOGNITION AND ENFORCEMENT OF FOREIGN JUDGMENTS IN ACCORDANCE WITH TURKISH INTERNATIONAL PRIVATE LAW - Liakopoulos, Dimitris (International Comparative Jurisprudence (Online), 2018)
The main purpose of this study is to present the conditions for the recognition and enforcement of foreign judgments in Turkey under Turkish law, with an emphasis on judicial decisions and a more follows reference to arbitration decisions. Due to the breadth of the subject, for which extensive literature has been developed in Turkish science as well as important jurisprudence, it has been considered appropriate to limit the coverage in this study to presenting the provisions of current Turkish law through its sources – notably the Code of Private International and Procedural Law (MÖHUK) – and the way in which it is interpreted and applied in both theory and Turkish law.